Reliability and validity of the Chinese Version of the Frequency, Intensity, and Burden of Side Effects Rating - Zhao, Jie; Ji, Junyu; Cao, Aiai; Ni, Jing; Cao, Tongdan (Frontiers in Psychiatry, 2025)
BackgroundThe Frequency, Intensity, and Burden of Side Effects Rating (FIBSER) Scale is a brief tool developed to assess side effects in patients with major depressive disorder (MDD). This study aims to evaluate the reliability and validity of the Chinese version of the FIBSER in Chinese patients with MDD.MethodsA total of 162 MDD patients were enrolled to assess the Chinese version of FIBSER, the self-report version of the Quick Inventory of Depressive Symptoms (QIDS-SR16), and the Rating Scale for Side Effects (SERS). Reliability and validity were evaluated using Cronbach’s α coefficient, test-retest reliability, Spearman correlation analysis, and Principal component analysis.ResultsThe Cronbach’s α coefficient for the Chinese version of the FIBSER was 0.945. The test-retest reliability coefficients for the three domains were 0.799, 0.821, and 0.897, respectively. The correlation coefficients between FIBSER and SERS ranged from 0.765 to 0.817. The correlation coefficients with QIDS-SR16 ranged from 0.187 to 0.270. Principal component analysis found one significant principal component, highlighting the prominence of side effect frequency as a factor. The Composite Reliability and Average Variance Extracted values in the confirmatory factor analysis showed excellent convergent validity.ConclusionsThe study suggests that the Chinese version of the FIBSER tool exhibits good reliability and validity in patients with MDD. It is suitable for the rapid clinical assessment of side effects in patients receiving antidepressant treatment.